1999
DOI: 10.1093/jac/43.3.373
|View full text |Cite
|
Sign up to set email alerts
|

A surveillance study of antimicrobial resistance of Gram-negative bacteria isolated from intensive care units in eight hospitals in Turkey

Abstract: This study was carried out with the participation of eight hospitals in Turkey to determine the frequency of gram-negative bacteria isolated in intensive care units (ICU) and to compare their resistance rates to selected antibiotics. Aerobic gram-negative bacteria isolated from ICUs during 1996 were studied. Antibiotic susceptibilities to imipenem, ceftazidime, ceftazidime-clavulanate, ceftriaxone, cefotaxime, cefepime, cefodizime, cefuroxime, piperacillin/tazobactam, amoxycillin-clavulanate, gentamicin, amika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
45
2
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 14 publications
12
45
2
4
Order By: Relevance
“…Respiratory pathogens are responsible for about one-third of ICU infections (Garner et al, 1998;Flanders, Collard, Saint, 2006). In the present study, the most common site of infection was the respiratory tract (51.7 %); this result is in agreement with other studies conducted indifferent countries including Turkey (38.8 %) (Gunseren et al, 1999), India (29.7%) (Orrett, 2002), Oman (65%) (Al-Lawati, Crouch, Elhag, 2000), Italy (91%) (Bassetti et …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Respiratory pathogens are responsible for about one-third of ICU infections (Garner et al, 1998;Flanders, Collard, Saint, 2006). In the present study, the most common site of infection was the respiratory tract (51.7 %); this result is in agreement with other studies conducted indifferent countries including Turkey (38.8 %) (Gunseren et al, 1999), India (29.7%) (Orrett, 2002), Oman (65%) (Al-Lawati, Crouch, Elhag, 2000), Italy (91%) (Bassetti et …”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the resistance rate to cephalosporins (79.5%-87.8%) was comparable to that in Iran (Hadadiet al, 2008), but higher than reported in foreign studies (Gunseren et al, 1999;Al-Lawati, Crouch, Elhag, 2000;Glupczynski et al, 2001;Patzer, Dzierzanowska,Turner, 2002;Gonlugur et al, 2004;Karlowsky et al, 2003;Meric et al, 2005). C u r r e n t r e s u l t s a l s o s h o w e d t h a t 2 5 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These microorganisms have survived for thousands of years by their ability to adapt to antimicrobial agents [10].…”
Section: Methicillin-resistantmentioning
confidence: 99%
“…(Shehabi et al, (1996), Ducel et al,(2002), Krishna et al,) Critically ill Intensive care unit (ICU) patients are most vulnerable for developing these infections . Compared with an average patient, an ICU patient has five to seven folds higher risk of nosocomial infection and ICU infections contributes to 20% to 25% of all nosocomial infections in a hospital (Günserena et al, 1999). Factors like increasing use of invasive devices, immunosuppressive drugs and status as well as irrational use of antibiotic therapy in ICUs are all contributing for the same.…”
Section: Introductionmentioning
confidence: 99%